Answer:
x = 1 , y = 8 thus: A. is your answer
Step-by-step explanation using substitution:
Solve the following system:
{y = 2 x + 6
y = 11 - 3 x
Hint: | Perform a substitution.
Substitute y = 2 x + 6 into the second equation:
{y = 2 x + 6
2 x + 6 = 11 - 3 x
Hint: | Choose an equation and a variable to solve for.
In the second equation, look to solve for x:
{y = 2 x + 6
2 x + 6 = 11 - 3 x
Hint: | Isolate x to the left hand side.
Subtract 6 - 3 x from both sides:
{y = 2 x + 6
5 x = 5
Hint: | Solve for x.
Divide both sides by 5:
{y = 2 x + 6
x = 1
Hint: | Perform a back substitution.
Substitute x = 1 into the first equation:
{y = 8
x = 1
Hint: | Sort results.
Collect results in alphabetical order:
Answer: {x = 1 , y = 8